A case of disseminated carcinomatosis of the bone marrow originating from gastric cancer 3 years after intraperitoneal chemotherapy against peritoneal carcinomatosis. Issue 1 (December 2016) - Okuno, Takayuki; Yamaguchi, Hironori; Kitayama, Joji; Ishigami, Hironori; Nishikawa, Takeshi; Tanaka, Junichiro; Tanaka, Toshiaki; Kiyomatsu, Tomomichi; Hata, Keisuke; Nozawa, Hiroaki; Kawai, Kazushige; Kazama, Shinsuke; et al.
Abstract Background Clinical studies of intraperitoneal chemotherapy with paclitaxel in patients of gastric cancer with peritoneal carcinomatosis is well tolerated and effective, and rare cases of metastasis and recurrence have experienced during the treatment. Disseminated carcinomatosis of the bone marrow is highly rare in gastric cancer and associated with a poor prognosis. Case presentation A 59-year-old woman of gastric cancer with peritoneal carcinomatosis received five courses of chemotherapy with intraperitoneal administration of paclitaxel, and laparoscopy showed disappearance of the peritoneal carcinomatosis. She subsequently underwent total gastrectomy, and the histopathological findings showed a complete response to the chemotherapy. Postoperatively, chemotherapy with intraperitoneal administration of paclitaxel was continued for 30 months, without apparent recurrence. However, the gastric cancer recurred as disseminated carcinomatosis of the bone marrow with disseminated intravascular coagulation, and we hence changed the chemotherapy regimen to weekly irinotecan. Remission was achieved, and she did not experience any major symptoms; however, she died 6 months after the diagnosis of disseminated carcinomatosis of the bone marrow. Conclusions Since intraperitoneal paclitaxel administration can strongly suppress peritoneal carcinomatosis of gastric cancer, careful attention should be paid not only to peritoneal recurrence but also for rare site metastases, such as bone marrow metastases.